Identify Financial Ratios to Measure The Company's Financial Performance - Syahnisa Sari Lubis (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2023)
This study aims to determine and analyze financial ratios as a tool to measure financial performance at PT. ABC is based on SOE and Theoretical Standards. This research approach is qualitative descriptive research, where qualitative descriptive research is analyzing data for problems of independent variables such as data in the form of numbers, generally not using statistics. The type of data in this study is qualitative data, namely data in the form of financial statements, namely profit/loss statements and balance sheet statements. This data collection technique is a documentation technique on secondary data sources of financial statements. The results of this study show that in the company PT. ABC shows that the financial performance of the calculation of liquidity ratios (current ratio and cash ratio) can be said to be good, and e financial performance of the calculation of solvency ratios (Debt to Equity Ratio and Debt to Asset Ratio) can be said to be good, financial performance from the calculation of profitability ratios (Return On Equity and Net Profit Margin) can be said to be less good, and financial performance from the calculation of activity ratios (Fixed Asset Turnover and Total Asset Turnover) It can be said to be not good.